2006
DOI: 10.1016/j.anireprosci.2005.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Histological and ultrastructural analysis of cryopreserved sheep preantral follicles

Abstract: The aim of this study was to verify the histological and ultrastructural characteristics of sheep preantral follicles after exposure of ovarian tissue to cryopreservation in glycerol (GLY), ethylene glycol (EG), propanediol (PROH) or dimethyl sulfoxide (DMSO) in order to determine the optimum method to store sheep ovarian tissue for later experimental or clinical use. Each ovarian pair from five mixed-breed ewes was divided into 17 fragments. One (control) fragment was immediately fixed for routine histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 46 publications
(55 reference statements)
3
36
1
Order By: Relevance
“…Unlike results previously reported in our studies in pigs [23], cattle [30], and sheep [19], DMSO was able to maintain the ultrastructure of preantral follicles enclosed in ovarian tissue after cryopreservation. In follicles included in ovarian tissue that were cryopreserved in the presence of EG, greater damage was observed in this study, manifested as reduced electron density and fewer organelles in the ooplasm.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike results previously reported in our studies in pigs [23], cattle [30], and sheep [19], DMSO was able to maintain the ultrastructure of preantral follicles enclosed in ovarian tissue after cryopreservation. In follicles included in ovarian tissue that were cryopreserved in the presence of EG, greater damage was observed in this study, manifested as reduced electron density and fewer organelles in the ooplasm.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar changes were reported following exposure of ovarian tissue of sheep [19] and goats [2,3] to 1.5 M concentrations of the same cryoprotectants.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, previous studies have shown the value of antioxidants in protecting ovarian tissue from ischemia following transplantation (Kim et al 2004) or their usefulness in freezing medium to improve follicular preservation (Melo et al 2011;Sanfilippo et al 2013). Vacuolization has been reported after cryopreservation of ovarian tissue from sheep (Santos et al 2006b;Oskam et al 2010), bovine (Celestino et al 2008) and human (Marsella et al 2008), with indications of damage in the ER (Silva et al 2000). In agreement with this evidence, Oskam et al (2010) found oocyte vacuolization together with an extreme decrease in or even total absence of smooth and rough ER in cryopreserved sheep ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-antral follicles were defined as follicles without an antrum. Follicular quality was evaluated based on the morphological integrity of the oocyte, the granulosa cells and the basement membrane as described previously (Santos et al 2006b). To avoid counting a follicle more than once, pre-antral follicles were counted in the sections in which their oocyte nucleus was observed.…”
Section: Morphology Of Ovarian Tissue Exposed To Fs (Experiments I)mentioning
confidence: 99%
“…This is in accordance with the results of other groups, who found DMSO to allow for better preservation of primary follicles than PrOH in human tissue (Gandolfi et al 2006), although no effects were found in the population of primordial follicles in that study. Other studies suggest that even though EG is known for its low toxicity when applied as a cryoprotectant of bovine and caprine ovarian tissue (Santos et al 2006b, Celestino et al 2008, DMSO preserves the ultrastructure of ovine early-staged follicles better (Santos et al 2006a).…”
Section: Discussionmentioning
confidence: 99%